The year of second chances - Avery, Lara (William Morrow, an imprint of HarperCollinsPublishers, 2023)
When she discovers that her late husband enrolled her in a dating service, which he set up to go into effect a year after his death, Robin Lindstrom puts herself out there and finds herself meeting new people, trying new things, and getting a second chance at love--and at loving life.